Efficient arabinoxylan assay for wheat: Exploring variability and molecular marker associations in Wholemeal and refined flour - Hernandez-Espinosa, Nayelli; Posadas-Romano, Gabriel; Dreisigacker, Susanne; Crossa, José; Crespo Herrera, Leonardo A.; Ibba, Maria Itria (Elsevier, 2024)
In this study, we present a modified high throughput phloroglucinol colorimetric assay for the quantification of arabinoxylans (AX) in wheat named PentoQuant. The method was downscaled from a 10 ml glass tube to 2 ml microcentrifuge tube format, resulting in a fivefold increase in throughput while concurrently reducing the overall cost and manual labor required for the analysis. Comparison with established colorimetric assays and gas chromatography validates the modified protocol, demonstrating its superior repeatability, rapidity, and simplicity. The effectiveness of the protocol was tested on 606 unique whole meal (WM) and refined flour (RF) bread wheat samples which revealed the presence of more than a twofold variation in both the soluble (WE-AX) and total (TOT-AX) AX fractions in WM (TOT-AX = 31.9–76.1 mg/g; WE-AX = 4.4–12.6 mg/g) and RF (TOT-AX = 7.7–22.4 mg/g; WE-AX = 3.9–11.4 mg/g). Results obtained from the AX quantification were used to test the effectiveness of four molecular markers associated with AX variation and targeting two major genomic regions on the 1BL and 6BS chromosomes. These markers appeared to be particularly relevant for the WE-AX fraction, providing insights to enable marker-assisted breeding.